A3.23 Vitamin D Antagonises the Suppressive Effect of Inflammatory Cytokines upon CTLA-4 Expression and Regulatory Function. (25th February 2013) - Jeffery, LE; Raza, K; Sansom, DM
Abstract : Background and Objectives: The suppressive protein, cytotoxic T lymphocyte antigen–4 (CTLA-4), is constitutively expressed by TRegs and induced in effector T cells upon activation. Its crucial role in adaptive immunity is apparent from the fatal autoimmune pathology of CTLA-4 knockout mice and the association of CTLA-4 genetic variants with autoimmunity. We have recently shown that CTLA-4 functions by depleting antigen-presenting cells of their co-stimulatory ligands, CD80 and CD86 (Qureshi et al, Science 2011). However, little is known about the factors that regulate CTLA-4 expression and function. Since low vitamin D status and elevated Th17 frequencies are evident in many autoimmune conditions, we have investigated the effect of vitamin D and Th17 polarising cytokines upon CTLA-4 expression and function. Methods: Peripheral blood CD4 + CD25 – T cells were stimulated under Th17 polarising conditions (TGFbeta, IL-1beta, IL-6 and IL-23) with or without active vitamin D (1.25(OH)2 D3 ). FoxP3 and CTLA-4 were measured by flow cytometry and the vitamin D receptor (VDR) by qPCR. To assess CTLA-4 function, T cells were cultured with anti-CD3 and cells expressing GFP-tagged CD86. CD86-GFP acquisition by T cells with or without CTLA-4 blockade was then monitored by flow cytometry. For suppression assays, separately labelled activated T cells and CD4 + CD25 − responder T cells were co-cultured with dendritic cells in the presence of anti-CD3 and T cell proliferation assessed at five days by flow cytometry. Results: Vitamin D increased CTLA-4 expression and the frequency of FoxP3+CTLA-4+ T cells. By contrast, Th17 polarising cytokines suppressed CTLA-4. Interestingly, when supplied together, Th17 polarising cytokines synergised with vitamin D resulting in significantly higher CTLA-4 expression than with vitamin D alone. This synergy corresponded with increased VDR expression under Th17 conditions. Using a novel assay to test CTLA-4 function, we further confirmed that these changes in CTLA-4 expression correlated with ligand removal. Moreover, in dendritic cell driven stimulations vitamin D-treated T cell blasts showed enhanced CTLA-4-mediated suppression. Conclusions: Vitamin D overrides the inhibitory effect of pro-inflammatory Th17 polarising cytokines upon CTLA-4 expression and function. Given the importance of CTLA-4-mediated suppression in the control of autoimmune diseases, including RA, these data highlight the importance of vitamin D in immune regulation and its potential as a therapeutic agent.